2015
DOI: 10.3791/52718
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency Ultrasound Imaging of Mouse Cervical Lymph Nodes

Abstract: High-frequency ultrasound (HFUS) is widely employed as a non-invasive method for imaging internal anatomic structures in experimental small animal systems. HFUS has the ability to detect structures as small as 30 µm, a property that has been utilized for visualizing superficial lymph nodes in rodents in brightness (B)-mode. Combining power Doppler with B-mode imaging allows for measuring circulatory blood flow within lymph nodes and other organs. While HFUS has been utilized for lymph node imaging in a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Limiting surgical resection would significantly reduce surgical complications and consequently result in an improved quality of life for the patient. Grey scale ultrasound imaging (US) has previously been used to identify and characterize the LNs adjacent to the primary tumor [4,[6][7][8]. Specifically with respect to rectal cancer, a meta-analysis of clinical studies undertaken between 1985 and 2005 demonstrated that endoluminal ultrasound was at least as good as MRI or CT for identification of nodal disease and that no significant difference between imaging modalities was measured with respect to the staging of nodal status [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limiting surgical resection would significantly reduce surgical complications and consequently result in an improved quality of life for the patient. Grey scale ultrasound imaging (US) has previously been used to identify and characterize the LNs adjacent to the primary tumor [4,[6][7][8]. Specifically with respect to rectal cancer, a meta-analysis of clinical studies undertaken between 1985 and 2005 demonstrated that endoluminal ultrasound was at least as good as MRI or CT for identification of nodal disease and that no significant difference between imaging modalities was measured with respect to the staging of nodal status [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al demonstrated that quantitative parameters such as short axis length, echogenicity, shape, and how distinct the lymph node margin were independent features capable of predicting lymph node metastasis in lung cancer patients [7]. In a highly detailed paper, Walk et al demonstrated the efficacy of high-resolution ultrasound for imaging and accurately reconstructing small structures such as mouse cervical lymph nodes in 3D [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we assessed the cellular and tissue-scale LN responses to 'strong' and 'weak' vaccines with distinct therapeutic outcomes. Vaccine-draining LNs (dLNs) were imaged longitudinally using high frequency ultrasound (HFUS), a simple, noninvasive technique for visualizing superficial internal structures with high (~20μm) axial resolution, to establish the magnitude and kinetics of LN response [14]. Gross LN expansion was then analyzed in comparison to outcomes of immunization (i.e.…”
Section: Introductionmentioning
confidence: 99%